Estrategias metodológicas utilizadas por los docentes de Lengua y Literatura de la Unidad Educativa Virgilio Abarca Montesinos para potenciar la comprensión lectora de textos literarios en estudiantes de octavo año de Educación General Básica Superior - Ordóñez González, Elizabeth del Rocío (2023)
The present investigation arises from the need to know correctly are the methodological strategies that teachers use to enhance reading comprehension in students. Therefore, the main objective of this research is to analyze the methodological strategies used by language and literature teachers from the Virgilio Abarca M. Educational Unit, located in the Urdaneta parish, Saraguro canton, Loja province, to develop reading comprehension in high school students. eighth year of Superior Basic General Education. The research was of a qualitative nature and the non-participant classroom observation and the semi-structured interview were used as data collection methods and as a technique for each of these the observation sheet and the questionnaire that were applied to two teachers of the Language Area and Literature. After the application of the instruments, it was found that the teachers to carry out the reading practice will be guided only by the Text of the Ministry of Education and the most used strategies to enhance reading comprehension are the summary and the underlining. At the end of the investigation, it was concluded that teachers, when reading a literary text, use the activities proposed in the text of the Ministry of Education as the only strategy; Since being the only strategy used generates students' lack of interest, then it is considered that the selection of methodological strategies should go hand in hand with the planning of each class so that these strategies help to meet the objectives set out in the National curriculum of Education. Keywords: reading comprehension, methodological strategies, reading, pre-reading, post-reading.